2020
DOI: 10.3390/f11050603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Invasive Rhododendron ponticum L. on Natural Regeneration and Structure of Fagus orientalis Lipsky Forests in the Black Sea Region

Abstract: Biological invasions threaten global biodiversity and forest ecosystems; therefore, it is necessary to use appropriate strategies for combating the spread of invasive species. Natural regeneration of eastern beech (Fagus orientalis Lipsky) is considerably limited by an aggressive invasive shrub, pontic rhododendron (Rhododendron ponticum L.), in the Black Sea Region of Turkey. Therefore, the future character of the region’s forests is uncertain. The aim of this research was to evaluate the structure of beech f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The vertical structure was evaluated according to the Gini index (Gini 1921) and the spatial distribution according to the index of cluster size (David & Moore 1954). The equations of diversity indices are given in Vacek et al (2020c).…”
Section: Discussionmentioning
confidence: 99%
“…The vertical structure was evaluated according to the Gini index (Gini 1921) and the spatial distribution according to the index of cluster size (David & Moore 1954). The equations of diversity indices are given in Vacek et al (2020c).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the density may be temporary (Schnitzer, Carson 2001) and may pass over time. For example, tree regeneration may be inhibited over time by disturbing plant layers or invasive species (Kern et al 2012;Vacek et al 2020). From our findings, it seems that man-made gaps have been created where advanced regeneration was present.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have emphasised the effect of the understory vegetation on the overall structure of the forest (Spies, Franklin 1991;Berger, Puettmann 2000;Sullivan et al 2001;Anderson, Meikle 2006;Dröβler 2006;Hinsley et al 2009;Nagel et al 2013;Feldmann et al 2018). Vacek et al (2020) showed that after three and six years of management (rhododendron clearance) in the Black Sea region Oriental beech forest (Fagus orientalis Lipsky) of Turkey, the number of natural regenerations increased from 63 981 ha -1 to 105 075 ha -1 .…”
mentioning
confidence: 99%
“…Their presence and influence may also facilitate the invasion of other non‐natives, especially in the understory (Kuebbing & Nuñez, 2015 ; O'Loughlin & Green, 2018 ). Such understory invasives can have cascading impacts by competing with natural forest regeneration (Dyderski et al, 2017 ; Vacek et al, 2020 ), impacting animal movements (Habel et al, 2016 ; Stewart et al, 2021 ), and enhancing edge effects (McDonald & Urban, 2006 ). Mapping such invasions at a landscape level becomes imperative to understand if particular overstory invasive species are associated with specific understory invasive species.…”
Section: Introductionmentioning
confidence: 99%